2016
DOI: 10.1016/j.virusres.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Anti-influenza virus activity of high-mannose binding lectins derived from genus Pseudomonas

Abstract: Lectin PFL binding high-mannose glycan derived from Pseudomonas fluorescens and other homologous lectins: PML derived from Pseudomonas mandelii and PTL derived from Pseudomonas taiwanensis were examined for antiviral activity. The cDNA of these lectin genes were synthesized, cloned, expressed in Escherichia coli. The expressed lectins were purified by gel filtrations, and supplied to cultures infected with several strains of influenza virus. These three lectins have inhibited propagation of influenza viruses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…As seen in Figure 3, the binding preference of HRL40 for the exposed (α1-3) Man residue was markedly severe among Type I lectin family, promising the utility of this lectin as a valuable tool in the fields of basic and applied glycomics. To be exact, HRL40 potently inhibited the entry of influenza virus (A/H3N2/Udorn/72) to NCI-H292 cells with ED 50 of 2.45 nM, which was the highest anti-influenza virus activity that we have ever examined for lectins [8,9,13,35]. In addition, the affinity constant (K D , 3.69 × 10 −11 M) of this lectin for the influenza virus envelope hemagglutinin was also remarkably high.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…As seen in Figure 3, the binding preference of HRL40 for the exposed (α1-3) Man residue was markedly severe among Type I lectin family, promising the utility of this lectin as a valuable tool in the fields of basic and applied glycomics. To be exact, HRL40 potently inhibited the entry of influenza virus (A/H3N2/Udorn/72) to NCI-H292 cells with ED 50 of 2.45 nM, which was the highest anti-influenza virus activity that we have ever examined for lectins [8,9,13,35]. In addition, the affinity constant (K D , 3.69 × 10 −11 M) of this lectin for the influenza virus envelope hemagglutinin was also remarkably high.…”
Section: Discussionmentioning
confidence: 92%
“…From the cDNA cloning of a cyanobacterial lectin, OAA, we presented that the genes coding Type I lectin proteins are widely distributed in lower organisms [6,12,29], including red algae and bacteria such as Myxococcus xanthus hemagglutinin (MBHA) [31], Pseudomonas fluorescens lectin (PFL) [32] and Burkholderia oklahomensis agglutinin (BOA) [33]. MBHA and PFL were confirmed to inhibit the HIV-infection in the host cells using their recombinants [34,35]. The Type I HM-specific lectins (the OAA family) consist of two or four tandem repeats of the conserved domain of 66-67 amino acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some classes of them are well-known high-mannose binding lectins (e.g., in the complement system, surfactant proteins A and D) (1,12,13). Since high-mannose glycans are predominant on viral surface proteins such as human immunodeficiency virus-1 (HIV-1) gp120 and influenza hemagglutinin (HA) protein, the antiviral activities of high-mannose binding lectins are well known (2,(14)(15)(16)(17). We previously reported that Oscillatoria agardhii agglutinin (OAA)-the family of lectins, although exogenous bacterial lectins unrelated to human C-type lectins, showed broad-spectrum antiviral activity against multiple strains of HIV and influenza virus with 50% inhibitory concentration (IC 50 ) in the nanomolar range (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that Oscillatoria agardhii agglutinin (OAA)-the family of lectins, although exogenous bacterial lectins unrelated to human C-type lectins, showed broad-spectrum antiviral activity against multiple strains of HIV and influenza virus with 50% inhibitory concentration (IC 50 ) in the nanomolar range (17)(18)(19). The antiviral activity was inhibited by the addition of yeast mannan (17), indicating that binding of the lectin to high-mannose glycans is committed to the activity. Antiviral activities of high-mannose binding lectins against hepatitis C virus (20, 21), coronavirus (22)(23)(24), Ebola virus (25,26), Japanese encephalitis virus (27), and others have been reported.…”
Section: Introductionmentioning
confidence: 99%